Efek Perilaku dan Persepsi Milenial terhadap Minat Menggunakan Mobile Banking Perbankan Syariah di Indonesia - Aisyah, Muniaty (Management Study Program, Faculty of Economic, Universitas Samudra, Indonesia, 2023)
The millennial generation dominates digital banking activity in Indonesia becauseof their dynamic behavior in accessing the internet. This study will analyze theeffects of Millennial behavior and their perception of Islamic banks on theirinterest in using its mobile banking with PLS analysis. The results showed thatonly Millennials' online behavior significantly influenced their perception ofIslamic banking and their interest in using mobile banking of Islamic banks, whileMillennials' financial behavior only influenced their interest in using it.Conversely, Millennial online transportation behavior does not affect eitherperception or interest in using mobile banking of Islamic banks. This study alsoshows that although Millennials' online and financial behavior significantly affectstheir interest in using mobile banking of Islamic banks, most Millennials prefer touse e-wallets such as Go-pay or OVO for their daily online transactions’ activitiesfor several different reasons.